Evaluation of the in vitro acaricidal activity of Chinese herbal compounds on the poultry red mite (Dermanyssus gallinae) - Jian, Yichen; Yuan, Huizhen; Li, Dongliang; Guo, Qing; Li, Xiaoying; Zhang, Sumei; Ning, Changshen; Zhang, Longxian; Jian, Fuchun (Frontiers in Veterinary Science, 2022)
The poultry red mite Dermanyssus gallinae is an economically important pest in poultry farms worldwide, but an effective treatment option is lacking. The current study determined the effectiveness of six Chinese herbal medicines [Syzygium aromaticum (clove), Hibiscus syriacus(Hibiscus), Illicium verum (star anise), Leonurus artemisia (motherwort), Cinnamomum cassia (cinnamon), and Taraxacum sp. (dandelion)] against D. gallinae. Alcohol extracts were prepared via the solvent extraction method and the phenol, flavonoid, and tannin contents were determined. These active components were highest in S. aromaticum and lowest in H. syriacus, I. verum. No tannin content was detected in L. artemisia. All extracts showed contact toxicity against D. gallinae at a test concentration of 1 g/mL, with S. aromaticum and L. artemisia resulting in 100% mortality. S. aromaticum, L. artemisia, and I. verum showed the best efficacy (LC50 0.159 g/mL, 0.200 g/mL and 0.292 g/mL, respectively). Different combinations of extracts showed an additive effect of I. verum LC90 + L. artemisia LC90. The acaricidal efficacy of this combination was tested against different developmental stages of D. gallinae, being most efficacious against nymphal and larval D. gallinae, with a corrected mortality rate of 100%. However, inhibition of egg hatching was only 53.69%. Taken together, these results highlight I. verum LC90 + L. artemisia LC90 as a promising compound with severe contact toxicity against D. gallinae. Given the wide cultivation of these species and their extensive use in foodstuffs and cosmetics as flavors and fragrances, they could be a cheap, readily available ecofriendly alternative to pesticides currently used in poultry farms.